(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The research project titled " Sounds in the Theater: terms and concepts" aims to collectively develop entries for a homonymous dictionary, unprecedented in the Lusophone world, through a terminological and conceptual investigation of the vocabulary of sound in performing arts. The project began in 2021 and currently involves 90 researchers affiliated with 38 educational institutions from all 5 (five) regions of the country. This article aims to present the main motivations, as well as the challenges and strategies that have permeated the process so far.